Study, Terchers' Strategy for Fostering Reading Habits Among High School Students: A Case Study at State of Junior High School in West Lombok - Aristawidya, Alzena; Fatmasari, Santi; Zamzam, Ahmad; Thohir, Lalu (Journal of English Language and Education, 2026)
This study explores the strategies employed by English teachers to foster reading habits among eighth-grade students and examines the challenges they encounter during the teaching and learning process. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and teacher questionnaires. The findings revealed that teachers implemented four main strategies to promote students’ reading habits: reading aloud, guided reading, silent reading, and providing motivation and vocabulary support. These strategies were applied adaptively, depending on students’ proficiency levels and classroom conditions. Despite their effectiveness in encouraging participation and improving engagement, teachers faced several obstacles, including students’ limited vocabulary, low motivation, inadequate learning media, and time constraints caused by curriculum demands. The study concludes that fostering reading habits requires not only creative and consistent teacher efforts but also strong collaboration among schools, families, and communities to provide a supportive reading environment.